PEMBINAAN WIRAUSAHA DALAM MENINGKATKAN PERKEMBANGAN USAHA MIKRO DAN KECIL (UMK) - MIRA VERANITA, RINI SUSILOWATI MIRA VERANITA, RINI SUSILOWATI (EKBIS (Ekonomi & Bisnis), 2018)
The purpose of this study is to determine the impact of entrepreneurship development on the development of micro and small enterprises. This research is quantitative research with explanatory research, with data collecting technique through questioner and interview and sample using saturated sample technique, with Quantitative analysis uses validity test, reliability test, simple regression analysis, coefficient of determination, significance test (t test). The results of this study indicate that the variables of entrepreneurship (X) have an effect on business development (Y) of 77.7%. Entrepreneurship development has a positive and significant influence on business development. Entrepreneurship development conducted by Lengkong Sub-district is to provide institutional guidance, human resource development, financing facility, introduction and development of technology application, production development, marketing and promotion facility and business protection, in the form of socialization, giving facility in the form of capital and non capital as well as various training and mentoring and product development.